MoDIp Development: Digital Science Module Based on Local Wisdom Containing Recitation Enhancing Students Digital Literacy - Sholehah*, Najah; Prahastiwi, Rima Buana; Qadafi, Muammar (Jurnal IPA & Pembelajaran IPA, 2025)
The limitations of the available science modules, because they have not integrated local wisdom and recitation in the contextual learning process to support students' digital literacy. This study aims for the development of a digital science module because it is based on local wisdom containing recitation for improvements to student digital literacy within the junior high school level. This type of research researches as well as develops through adaptation of the four-D (4D) model with a qualitative approach regarding product trials. 4D has 4 stages that are definition, design, develop, also to disseminate. The design of the digital science module is on a local wisdom base. That program contains local wisdom of Sembalun Village, East Lombok, West Nusa Tenggara. The digital module's validity, practicality, and effectiveness were each put to a test. Experts on materials confirmed the test having 93.75% in a feasible category. Experts in media plus experts in recitation programs validated it, with 96.42% and 95% in a feasible category. The teachers' practical test showed 96% very practical as the students' small scale field trial showed 96% very feasible. The next test checks whether the digital science module effectively improves students' digital literacy since researchers measured it qualitatively, gaining an N-Gain of 0.54. Results from the t-test are at 0.008, meaning digital literacy increased differently before and after the learning. The novelty in this study is the local wisdom-based science digital module strengthens the digitalization of student learning and recitation contextually and holistically. This research includes local wisdom material and strengthening student recitation in learning